2022
DOI: 10.1007/s00424-021-02656-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional subgroups of rat and human sensory neurons: a systematic review of electrophysiological properties

Abstract: Sensory neurons are responsible for the generation and transmission of nociceptive signals from the periphery to the central nervous system. They encompass a broadly heterogeneous population of highly specialized neurons. The understanding of the molecular choreography of individual subpopulations is essential to understand physiological and pathological pain states. Recently, it became evident that species differences limit transferability of research findings between human and rodents in pain research. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Sensory neurons in the DRG are extremely diverse depending on their size, expression, and signaling activity (Körner and Lampert, 2022 ). Because each neuron has a sheath consisting of SGCs, the diversity of neurons is accompanied by a variety of SGCs consisting of this sheath.…”
Section: Heterogeneity Of Satellite Glial Cellsmentioning
confidence: 99%
“…Sensory neurons in the DRG are extremely diverse depending on their size, expression, and signaling activity (Körner and Lampert, 2022 ). Because each neuron has a sheath consisting of SGCs, the diversity of neurons is accompanied by a variety of SGCs consisting of this sheath.…”
Section: Heterogeneity Of Satellite Glial Cellsmentioning
confidence: 99%
“…There are a number of advantages with our approach over previous studies. Previous studies used in vivo intracellular recordings and demonstrated distinct electrophysiological properties of Aβ-afferent neurons in DRGs and their response to mechanical stimulation applied to the periphery ( Korner and Lampert 2022 ). However, in vivo intracellular recordings provided limited information about ion channels involved in mechanical and chemical sensitivity of Aβ-afferent neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The somas of somatosensory afferents are located in the dorsal root ganglions (DRGs) and trigeminal ganglions (TGs), which vary in sizes with small-to medium-diameter neurons giving rise to C- and Aδ-afferents and large-diameter neurons giving rise to Aβ-afferents ( Vermeiren et al 2020 ). Functions of somatosensory afferents are commonly studied by making electrophysiological recordings from the somas of these nerves or afferent neurons ( Korner and Lampert 2022 ). C-and Aδ-afferent neurons have been extensively studied, and most of them are involved in nociception induced by high-intensity mechanical, thermal, and chemical stimulation ( Korner and Lampert 2022 ; Lawson et al 2019 ; Vermeiren et al 2020 ), although some Aδ- and C-afferents are low threshold mechanoreceptors (LTMRs) for sensing touch ( Djouhri 2016 ; Li et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic review of available literature identified five grouping criteria for classification of rat DRGs. No sufficient number of data are available for human DRG neurons; however, it is clear that findings from rat neurons cannot be transferred offhand to the human system [8]. Further functional data on human sensory neurons are needed to facilitate progress in development of pain treatment.…”
mentioning
confidence: 99%